SISTEM PENDETEKSI INDIKASI KEBAKARAN DALAM RUANGAN DENGAN PENAMPIL MELALUI RASPBERRY PI - Rema Hindarko; Arief Hendra Saptadi; Sigit Pramono (MEDIA ELEKTRIKA, 2016)
The development of technology is now growing very rapidly. It encourages people to create something that could provide convenience to perform a task. One of them is able to monitor and detect fires from long distance. A house fire is a frequently-occured disaster in the community. It can be caused by environmental factors as well as carelessness of the home owner. Home fires often occur when there is noone at home. They can occur at anytime because it is a disaster that goes unexpected. This research aims to design a fire detection system using a temperature sensor and smoke sensor that can provide an indication of fire early on in a room. The design of this system consists of a temperature sensor, smoke sensor and Arduino microcontroller system which is able to transmit datafrom the temperature and smoke sensor to Raspberry Pi via serial communication. The results were shown in Raspberry Pi through a GUI display. It is suggested that the system uses security camera or web camera for precise monitoring and adds notification feature via SMS or other means through internet. Keywords: Raspberry Pi, Email, smoke, temperature, fire.